A multi-epitope vaccine GILE against Echinococcus Multilocularis infection in mice - Zhou, Pei; Zhou, Zhen; Huayu, Meiduo; Wang, Lei; Feng, Lin; Xiao, Yang; Dai, Yao; Xin, Mingyuan; Tang, Feng; Li, Runle (Frontiers in Immunology, 2023)
Abstract Objective: The objective of this study is construct a multi-epitope vaccine GILE containing B-cell and T-cell epitopes against Echinococcus Multilocularis (E. multilocularis) infection based on the dominant epitopes of E. multilocularis EMY162, LAP, and GLUT1. Methods: The structure and hydrophobicity of GILE were predicted by SWISS-MODEL, pyMOL, SOPMA and VMD, and its sequence was optimized by OptimumTM Codon. The prepared GILE gene was inserted into pCzn1 and transformed into Escherichia coli Arctic express competent cells. IPTG was added to induce the expression of recombinant proteins. High-purity GILE recombinant protein was obtained by Ni-NTA Resin. BALB/c mice were immunized with GILE mixed with Freund's adjuvant, and the antibody levels and dynamic changes in serum were detected by ELISA. Lymphocyte proliferation was detected by MTS. The levels of IFN-γ and IL-4 were detected by ELISpot and flow cytometry (FCM). CD4+ and CD8+ T cells were detected by FCM. The growth of hepatic cysts was evaluated by Ultrasound and their weights were measured to evaluate the immune protective effect of GILE. Results: The SWISS-MODEL analysis showed that the optimal model was EMY162 95-104―LAP464-479―LAP495-510―LAP396-410―LAP504-518―EMY162112-126. The SOPMA results showed that there were Alpha helix (14.88%), Extended strand (26.25%), Beta turn (3.73%) and Random coil (45.82%) in the secondary structure of GILE. The restriction enzyme digestion and sequencing results suggested that the plasmid pCzn1-GILE was successfully constructed. The SDS-PAGE results indicated that the recombinant protein was 44.68 KD. The ELISA results indicated that mice immunized with GILE showed higher levels of serum antibodies compared to the PBS group. The FCM and ELISpot results indicated that mice immunized with GILE secreted more IFN-γ and IL-4. Immunization with GILE also led to a significant decrease in the maximum diameter and weight of cysts and stimulated the production of CD4+ and CD8+ T-Cell. Conclusion: A multi-epitope vaccine GILE with good immunogenicity and antigenicity has been successfully constructed in this study, which may provide important theoretical and experimental bases for the prevention and treatment of E. multilocularis infection.